Analisis Yuridis Peran Amicus Curae Dalam Sengketa Hasil Pilpres Di Mahkamah Konstitusi (Studi Kasus : Perkara PHPU.PRES/XXII/2024) - Meita Lefi; Dola Riza; Rani Fepriana (Normative Jurnal Ilmiah Hukum, 2026)
The dispute over the 2024 Presidential Election (Pilpres) results at the Constitutional Court (MK) has become a public spotlight, particularly with the emergence of the amicus curiae phenomenon, or "friend of the court." This study analyzes the legal role of amicus curiae in the context of the 2024 Presidential Election PHPU (Public Order Dispute Resolution) trial. Although already present in Indonesian legal practice, the involvement of amicus curiae on an unprecedented scale in this PHPU case is an interesting phenomenon to study. Using normative methods with a qualitative approach, this study analyzes trial documents, Constitutional Court decisions, as well as media coverage and official statements related to the submission of amicus curiae. The results show that the submission of 48 amicus curiae reflects high public participation and concern for the integrity of democracy and justice. However, the role of amicus curiae remains facilitative and not binding on the judges' decisions. Their presence serves as voices of public interest, provides additional legal and factual perspectives, and encourages judges' accountability in deciding crucial cases. This study concludes that the amicus curiae phenomenon in the 2024 Presidential PHPU sets an important precedent for increasing public participation in the oversight of constitutional judicial processes in Indonesia, while also highlighting the potential and challenges of amicus curiae arrangements in the future.